Integrated Forage Production Methods in the Ethiopian Highlands - Mekonnen, Kindu; Bezabih, Melkamu; Assefa, Getnet; Adie, Aberra; Gebreyes, Million (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Training Workshop on Climate Smart Livestock Feed and Forage Innovations